Beijing’ s paired assistance program: Mitigating vulnerability, fostering development, and promoting equality in its ecological conservation areas - Guangcai Xu; Jiahui Zhang; Mingyi Xie; Haixia Du; Mengqi Guo (PLoS ONE, 2025)
Interregional cooperation is an important mechanism for promoting regional equality. The paired assistance policy (PAP) has been broadly used to address regional inequality in China. In Beijing, developed plain districts have been paired, one-to-one, with less developed ecological conservation areas (ECAs) in mountainous regions to promote green development and livelihood improvements. In these pairings, lateral inputs from developed regions such as financial inputs, industrial assistance, human resource training, etc., are provided to the ECAs. To analyse the effect of Beijing PAP implementation, the 2013–2022 vulnerability index from each district in the ECAs was evaluated with the Vulnerability-Scoping-Diagram (VSD) model to reflect the changes in the ecological environment before and after PAP implementation. The Propensity Score Matching Difference-in-Differences model (PSM-DID) was used to explore the impact of the PAP mechanism on the green development and livelihoods of rural residents in ECAs. The results revealed that the vulnerability index of the ECAs decreased from 0.45 in 2013 to less than 0.05 in 2022, with an average annual reduction of 9%, attributing to the strict implementation of environment preservation policies. The PAP mechanism also clearly promoted green economy and livelihoods development in the ECAs. In addition to effectively stimulating development in Beijing ECAs, the PAP mechanism can be referenced by similar metropolitan cities to develop regional collaboration for ecological protection and balanced development.